Effect of plant nutritional traits on the diet of grasshoppers in a wetland of Northern Patagonia. Issue 4 (24th September 2021) - Amadio, María Emilia; Pietrantuono, Ana Laura; Lozada, Mariana; Fernández-Arhex, Valeria
Abstract: Dichroplus maculipennis is one of the most damaging grasshoppers of wetlands. We investigated their feeding behavior in relation to the most abundant plants of Patagonian wetlands. Results showed that D. maculipennis was able to select its food resources and displayed a mixed diet. The most consumed plant was Taraxacum officinale, which contains a large amount of protein and water. However, consumption decreased when offered simultaneously with Juncus balticus and Holcus lanatus . Therefore, diet varied according to the supply of plants that were offered. In future studies, it would be interesting to analyze the influence of diet on performance.